Folk of the Air: The Wicked King - Book 2 - Black, Holly (New York ; Little, Brown and Company, 2019)
As seneschal to High King Cardan, Jude must fight to keep control of the Faerie throne while her younger brother, Oak, enjoys the childhood she never knew.
Keywords: Fairies -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Orphans -- Juvenile fiction; Princes -- Juvenile fiction; Courts and courtiers -- Juvenile fiction; Fantasy fiction; Fairies -- Fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Princes -- Fiction; Courts and courtiers -- Fiction